2008
DOI: 10.3892/ijmm.21.5.645
|View full text |Cite
|
Sign up to set email alerts
|

p53-related apoptosis resistance and tumor suppression activity in UVB-induced premature senescent human skin fibroblasts

Abstract: Abstract. Chronic exposure to solar UV irradiation leads to photoaging, immunosuppression, and ultimately carcinogenesis. Cellular senescence is thought to play an important role in tumor suppression and apoptosis resistance. However, the relationships among stress-induced premature senescence (SIPS), tumorigenesis and apoptosis induced by UVB remain unknown. We developed a model of UVB-induced premature senescence in human skin fibroblasts (HSFs). After five repeated subcytotoxic UVB exposures at a dose of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 39 publications
3
55
0
Order By: Relevance
“…Instead, the mutation on p53 leading to the lack of apoptosis and the strong induction of cell cycle arrest and senescence may be the main contributor to hypersensitivity to UVB. Consistent with this, a recent study linked chronic UV exposure to premature senescence in human skin fibroblasts, 23 which may have direct impact on UV induced photoaging. Further research is required to investigate the role of p53-dependent apoptosis in UV-induced inflammation and immunosuppression.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Instead, the mutation on p53 leading to the lack of apoptosis and the strong induction of cell cycle arrest and senescence may be the main contributor to hypersensitivity to UVB. Consistent with this, a recent study linked chronic UV exposure to premature senescence in human skin fibroblasts, 23 which may have direct impact on UV induced photoaging. Further research is required to investigate the role of p53-dependent apoptosis in UV-induced inflammation and immunosuppression.…”
Section: Discussionsupporting
confidence: 61%
“…19,20 Previous work revealed that in the absence of one or both alleles of p53, mice exhibit extreme sensitivity to tumor induction by UVB and a drastic decrease of apoptosis in the dermis. 21,22 More recent studies underline UVB as an inducer of p53-mediated premature cellular senescence 23,24 …”
mentioning
confidence: 99%
“…As previously described (15)(16)(17)(18)26), four F36T12 ERE-VHO UV tubes were used in this study as the UV source. A Kodacel TA401/407 filter was mounted 4 cm in front of the tubes to block UVC (wavelengths below 290 nm).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, UV irradiation also activates growth factor receptors, which induce the activation of protein kinase cascades such as the MAP kinase (MAPK) signal transduction pathways in the cells (14)(15)(16)(17)(18). The MAPK signaling pathways regulate a variety of cellular functions, including the expression of MMPs and the inhibition of collagen production, which interferes with the metabolism of extracellular matrix (ECM) and causes the characteristic changes of photoaging in histo- (11,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, differences in ECM production and matrix metalloproteinase (MMP) gene expression have been described between skin and oral mucosa fibroblasts, suggesting a different fibroblast phenotype depending upon the tissue of residence (11,12) . Studies analyzing the effects of UVB light on cultured skin fibroblasts showed that repeated exposure to subcytotoxic doses of UVB induces premature senescence (13) , resulting in a sharp decrease in cell proliferation (14) . In addition, UVB exposure of skin fibroblasts stimulates the expression of several cell cycle regulatory genes, such as p53, as well as, pro-inflammatory genes, such as COX-2 (14,15) .…”
Section: Introductionmentioning
confidence: 99%